Growing Old in an Older Brazil : Implications of Population Ageing on Growth, Poverty, Public Finance, and Service Delivery - Gragnolati, Michele; Jorgensen, Ole Hagen; Rocha, Romero; Fruttero, Anna (World Bank, 2012)
This chapter introduces the main issues associated with population aging, many of which will be investigated in detail throughout the volume. The next section describes the demographic transformation that Brazil has been experiencing and highlights its specific features, including a very rapid population aging process in the next few decades. Then the main economic framework behind this work, the life cycle theory according to which individuals' economic behavior varies according to their age, is discussed. The section after that introduces the first and second demographic dividends associated with the changing population age structure that accompanies the demographic transition of any country. Next covered is how poverty is linked to the life cycle in Brazil and the role of public transfers in reducing poverty among different age groups, followed by an investigation of how public expenditures vary across age groups and generations and what makes Brazil distinct from comparable OECD (Organization for Economic Co-operation and Development) and Latin American countries. Concluding the chapter are the main findings of the report.